2010
DOI: 10.3109/08037051003802541
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between hypertension and salt intake in Turkish population: SALTURK study

Abstract: This population-based epidemiological study was aimed to evaluate the daily salt intake and its relation to blood pressure in a representative group of Turkish population. The enrolled normotensive and hypertensive individuals (n = 1970) completed a questionnaire including demographics, dietary habits, hypertension awareness and drug usage. Blood pressure was measured and to estimate salt consumption, 24-h urine samples were collected. The daily urinary sodium excretion was 308.3 ± 143.1 mmol/day, equal to a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
3
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(81 citation statements)
references
References 30 publications
2
63
3
13
Order By: Relevance
“…SALTURK study (Erdem et al, 2010) performed in Turkey showed that salt consumption calculated from urine salt excretion was much higher than (18.04 ± 8.34 g/day/person) the recommended salt consumption of WHO (<5 g/day/person) (WHO, 2006).…”
Section: Discussionmentioning
confidence: 86%
“…SALTURK study (Erdem et al, 2010) performed in Turkey showed that salt consumption calculated from urine salt excretion was much higher than (18.04 ± 8.34 g/day/person) the recommended salt consumption of WHO (<5 g/day/person) (WHO, 2006).…”
Section: Discussionmentioning
confidence: 86%
“…However, the SALTURK study showed that daily salt consumption was approximately 18 g/day (daily urinary sodium excretion was 308.3 ± 143.1 mmol/day) in the general Turkish population (21). In a recent study from Turkey on 373 chronic kidney disease patients from stages 1-5, average daily salt intake was reported as nearly 10 g/ day (22).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with hypertension were recruited from three population-based field studies (Hypertension Incidence in Turkey study, 11 Salt Intake and Blood Pressure in Turkey study, 12 and one unpublished study) conducted by the Turkish Society of Hypertension and Renal Diseases. All of the above-mentioned studies used a two-stage stratified sampling method to select a nationally representative sample of the adult population over 18 years of age.…”
Section: Study Design and Participantsmentioning
confidence: 99%